STRATEGI PENGEMBANGAN PRASARANA DAN SARANA OBJEK WISATA DANAU MARAMBE KABUPATEN MANDAILING NATAL - Habibah, Nur; Yuliana, Yuliana; Kasmita, Kasmita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
This research aims to determine the strategy of development of infrastructure and facilities that have internal indicators is strengths andÂ weaknesses and than external indicators opportunities and threats. Research was descriptive with qualitative and quantitative data. Data was collected by using interviews, observation, documentation and questionnaires (questionnaires) involving informants and respondents. using Snowball Sampling and Sampling technique incidental. Infrastructure and facilities development strategy of This research aims to determine the strategy of development of infrastructure and facilities that have internal indicators is strengths andÂ weaknesses and than external indicators opportunities and threats. Research was descriptive with qualitative and quantitative data. Data was collected by using interviews, observation, documentation and questionnaires (questionnaires) involving informants and respondents. using Snowball Sampling and Sampling technique incidental. Infrastructure and facilities development strategy of